2016
DOI: 10.1080/10401334.2016.1155459
|View full text |Cite
|
Sign up to set email alerts
|

Health-Related Anxiety and Hypochondriacal Concerns in Medical Students: A Cross-Sectional Study From Pakistan

Abstract: In total, 513 medical students (66% female) participated. Their mean age was 21 ± 1.6 years. Three hundred seventy-five students (73%) reported having visited a doctor at least once in the past 6 months. Fifty students (9.9%) admitted to having addictions. The overall prevalence of significant hypochondriacal concerns was 11.9% (61 students). The presence of addiction was associated with a greater likelihood of developing significant health-related anxiety (odds ratio = 3.82, p = .003), 95% confidence interval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
23
3
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 28 publications
3
23
3
1
Order By: Relevance
“…As the public was only beginning to recognize this problem among health science students at that time, these early studies may have yielded exaggerated results by paying excessive attention to the phenomenon and using more liberal diagnostic criteria to attract more consideration. Zahid [29], by contrast, determined that only 11.9% of health science students met the criteria for hypochondriasis, which is low compared to the estimates of our review and previous reports. All available studies reported a higher prevalence of hypochondriasis among health science students than among the general population, where the approximate prevalence is 5.7% [23]; this indicates that hypochondriasis is a noteworthy issue among health science students.…”
Section: Discussioncontrasting
confidence: 91%
See 1 more Smart Citation
“…As the public was only beginning to recognize this problem among health science students at that time, these early studies may have yielded exaggerated results by paying excessive attention to the phenomenon and using more liberal diagnostic criteria to attract more consideration. Zahid [29], by contrast, determined that only 11.9% of health science students met the criteria for hypochondriasis, which is low compared to the estimates of our review and previous reports. All available studies reported a higher prevalence of hypochondriasis among health science students than among the general population, where the approximate prevalence is 5.7% [23]; this indicates that hypochondriasis is a noteworthy issue among health science students.…”
Section: Discussioncontrasting
confidence: 91%
“…Although numerous studies have shown that health science students have more easy access to medical resources and do not avoid seeking medical care when suffering pain or potential dysfunction [9,26], some researchers have found that they do not seek reassurance more frequently than non-health-science students [4,6,27]. Their perceptions of the medical profession [28] and the time required to receive medical services [29] influence students’ healthcare-seeking behaviors. With these findings in mind, whether health science students seek medical services when they have hypochondriac symptoms remains unclear, and it is worthwhile to explore what contributes to the inconsistency.…”
Section: Introductionmentioning
confidence: 99%
“…6 Medical students are more likely to develop illness anxiety disorder because of their increased probability to link symptoms and signs of serious medical conditions they are studying with their body sensations or other minor symptoms. [7][8][9] This has been attributed to the combined effect of intensive exposure to medical and clinical knowledge and the psychological pressure caused by the study load. These factors are thought to affect symptom detection and interpretation.…”
mentioning
confidence: 99%
“…Limited studies in the Eastern Mediterranean region revealed that the prevalence of the disorder varies from 11.9% to 16%. (6,7). The present study aimed to investigate the frequency and related factors of medical students' syndrome among medical students in Kerman University of medical sciences (KMU), Kerman province, Iran.…”
mentioning
confidence: 99%